Association of interleukin-36α and interleukin-38 with type 2 diabetes mellitus and diabetic neuropathy - Shahad W. Nassurat; Isam N. Salman; Ali H. Ad'hiah (SpringerOpen, 2024)
Abstract Background Interleukin (IL)-36α and IL-38, two novel cytokines of the IL-1 family, have recently been proposed to have a pathophysiological significance in type 2 diabetes mellitus (T2DM). However, there is a paucity of information regarding their association with diabetic neuropathy (DNP). Therefore, this study aimed to explore these interleukins in T2DM without and with DNP, referred to as T2D and DNP, respectively. The predicted interaction of IL-36α and IL-38 with other proteins was also analyzed bioinformatically. In this study, 85 T2D patients, 21 DNP patients, and 109 controls were recruited. Serum IL-36α and IL-38 concentrations were measured with ELISA kits. Results Median (interquartile range) of IL-36α concentrations was significantly greater in T2D and DNP patients compared with controls (62 [54-84] and 52 [45-56] vs. 44 [36-47] pg/mL, respectively; p < 0.001). T2D patients also exhibited significantly greater concentrations of IL-36α than DNP patients (p = 0.004). IL-38 concentrations were significantly greater in T2D and DNP patients compared with controls (208 [149-249] and 200 [130-253] vs. 64 [47-92] pg/mL, respectively; p < 0.001), while T2D and DNP patients showed no significant differences in IL-38 concentrations (p = 0.509). Both cytokines were reliable biomarkers in differentiating diabetic patients from controls, but differentiation performance was better in T2D (area under the curve [AUC] = 0.921 and 0.951, respectively) than in DNP (AUC = 0.881 and 0.844, respectively). Up-regulated IL-36α and IL-38 concentrations were significantly associated with a higher risk of T2D (37.92- and 29.97-fold, respectively) and DNP (10.11- and 32.47-fold, respectively). IL-36α was positively correlated with IL-38 in T2D (correlation coefficient [r s] = 0.487; p < 0.001), but a stronger correlation was found in DNP (r s = 0.683; p < 0.001). IL-36α and IL-38 showed predicted interactions with several cytokines and cytokine receptors of the IL-1 family. Conclusions IL-36α and IL-38 concentrations were upregulated in the serum of T2D and DNP patients. Both cytokines were indicated to be potential discriminating biomarkers associated with higher risk of T2D and DNP. Targeting the axis of their interaction with other cytokines of the IL-1 family may be important for understanding the pathophysiology of T2D and DNP.